HIV self-testing among high-risk men who have sex with men in China: a cross-sectional study. (October 2016) - Qin, Yilu; Liu, Fengying; Tang, Weiming; Tang, Songyuan; Liu, Chuncheng; Mao, Jessica; Wei, Chongyi; Tucker, Joseph
Abstract: Background: HIV self-testing holds great promise for reaching high-risk key populations who do not access facility-based services, but it has rarely been evaluated outside of structured research settings. HIV self-testing is a process by which a person takes and interprets a test. We aimed to characterise implementation of unsupervised HIV self-testing among men who have sex with men (MSM) in China. Methods: We undertook a nationwide online survey of MSM in November, 2015, in China. Men were invited to participate by clicking through banner adverts on social network sites. Eligible men were at least 16 years of age, had ever had anal sex with a man, and had had sex without use of a condom in the past 3 months. Among MSM who ever self-tested for HIV, we assessed benefits (eg, first-time HIV test, increased testing frequency, confirmatory testing) and adverse outcomes, (eg, coercion, violence, suicidality). First-time HIV test was defined by what an individual reported was their first ever test for HIV (a self-test or a facility test). Among MSM who reported ever testing for HIV, we identified correlates of HIV self-testing as first-time HIV test with use of multivariable logistic regression. The institutional review boards of the Guangdong Provincial Center for Skin Diseases and STI Control, the University of North Carolina at Chapel Hill, and the University of California San Francisco approved this study. Findings: Of 1610 eligible men, 1189 (73·9%) completed the survey. 28·7% (341/1189) reported ever self-testing for HIV. The HIV prevalence among self-testers was 7·0% (24/341) and among non-self-testers was 4·9% (15/306). Among self-testers, 58·7% (200/341) reported HIV self-testing as a first-time HIV test and 22·6% (77/341) had increased testing frequency. 77·5% (31/40) of those with a positive HIV self-test received confirmatory facility-based testing. Minimal adverse outcomes were noted. Multivariable analysis showed that self-testing as first-time HIV test was associated with younger age (odds ratio 0·95, 95% CI 0·91–0·99), not telling health-care providers about having sex with men (2·22, 1·56–3·17), not using the internet to meet sex partners (2·53, 1·45–4·43), and having group sex (1·76, 1·03–2·98). Interpretation: HIV self-testing increases first-time HIV testing and testing frequency among those with previous testing. This tool could be useful to scale up HIV testing among high-risk men in China and other settings. Funding: National Institutes of Health (NIAID 1R01AI114310-01), UNC-South China STD Research Training Center (FIC 1D43TW009532-01), UNC Center for AIDS Research (NIAID 5P30AI050410-13), UCSF Center for AIDS Research (NIAID P30 AI027763), NIMH (R00MH093201), Fulbright-Fogarty Fellowship (FIC R25TW0093), and SESH Global.